2010
DOI: 10.1007/s10344-010-0459-9
|View full text |Cite
|
Sign up to set email alerts
|

Born to cope with climate change? Experimentally manipulated hatching time does not affect duckling survival in the mallard Anas platyrhynchos

Abstract: Two main hypotheses proposed to explain the seasonal decline in reproductive performance in birds are (1) deterioration of environmental conditions and (2) lower parental quality of late breeders. Previous experimental work addressing these hypotheses generally have problematic biases pertaining to delay of hatching, costs of re-laying and incubation, as well as variation in the quality of eggs, territories, offspring and parental traits. We address these biases in an experimental test of the timing hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 79 publications
(105 reference statements)
0
11
1
Order By: Relevance
“…On the other hand, ectothermic organisms, like insects, are able to rapidly adjust their development and emergence to the prevailing temperatures, whereas homoeothermic organisms, such as waterfowl, are less likely to evolutionary respond to such changes (Buse et al 1999, Winkler et al 2002. However, some waterfowl, e.g., mallard, are often considered to be relatively flexible in their breeding time (Sjoberg et al 2011, Drever et al 2012. We show here that this is, at least partly, true since both mallard and coot seem to delay their breeding during very cold winters, but, in contrast, show negligible adjustments at temperatures above 78C (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ectothermic organisms, like insects, are able to rapidly adjust their development and emergence to the prevailing temperatures, whereas homoeothermic organisms, such as waterfowl, are less likely to evolutionary respond to such changes (Buse et al 1999, Winkler et al 2002. However, some waterfowl, e.g., mallard, are often considered to be relatively flexible in their breeding time (Sjoberg et al 2011, Drever et al 2012. We show here that this is, at least partly, true since both mallard and coot seem to delay their breeding during very cold winters, but, in contrast, show negligible adjustments at temperatures above 78C (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, behavioral traits can be an area for exploring adaptation strategies. Sjöberg et al (2011) [25] examined CC impacts on wild mallard ducks in northern Sweden. They found that moderate CC had minor effects on duckling survival and this could be due to a trait that copes with CC.…”
Section: Non-ruminantsmentioning
confidence: 99%
“…Drever and Clark's () results and ours together suggest that breeding ducks have considerable flexibility to tolerate variation in spring earliness (see also Sjöberg et al . ). This is also consistent with findings by Oja and Pöysä () for Mallard in two study areas in Finland.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, a decrease in brood size with the length of the interval from ice break‐up to hatching may mirror the general pattern found in birds (including many duck species) of a seasonal decline in reproductive performance (for hypotheses and examples see Sjöberg et al . ). If the timing of breeding does not affect duckling survival, as was experimentally demonstrated in Mallard (Sjöberg et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation